PENGETAHUAN, SIKAP, PERILAKU DAN SARANA SANITASI PENDERITA DIARE DI WILAYAH KERJA SALAH SATU PUSKESMAS DI BANJARNEGARA - Adilatu Nurillah; Joko Malis Sunarno; Dwi Atin Faidah (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2024)
Diarrhea is an endemic disease in Indonesia and potential for repeatedly happens which accompanied by death. The purpose of this study was to describe the knowledge attitudes behavior and sanitation facilities of diarrhea patients in the working area of one of Public Health Center in Banjarnegara. This study was descriptive with a cross-sectional approach. The population in this study was diarrhea sufferers who had checked themselves into the public health center in the period from January to March 2022, namely 31 people with a total sampling technique. Data used in this study were obtained from questionnaires and field observations as well as data from the public health center. The results showed that most of male respondent were 51.6% with ages between 0-5 years in 41.9%. The good level knowledge of respondents were 51.6%, good level of attitude of respondents were 74.1%, positive behave respondents were 100%. Most of respondents' availability of latrines met the requirements in 80.6%, the availability of clean water mostly met the requirements in 87% and the physical quality of the water used mostly met the requirements in 77.4%. It can be seen that diarrhea sufferers have good knowledge, good attitude, positive behavior and the availability of sanitation facilities for most respondents. Respondets are expected to be able to apply a healthy lifestyle and get more inportant information from health workers to improve their health.